2001
DOI: 10.1007/s004640080158
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic intragastric stapled resection of gastric submucosal tumors located near the esophagogastric junction

Abstract: Although we need to evaluate the long-term outcomes, our procedure is considered technically feasible, safe, and useful for the resection of gastric submucosal tumors located near the esophagogastric junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 19 publications
2
71
0
7
Order By: Relevance
“…Finally, two small series have suggested a role for a combined endoscopic and laparoscopic approach, using two or three intragastric trocars. This proved feasible for resection of GISTs of the oesophagogastric junction 42,43 . Still, it is a technically demanding procedure that requires advanced laparoscopic skills and instrumentation.…”
Section: Lesser Curvature and Gastro-oesophageal Junctionmentioning
confidence: 99%
“…Finally, two small series have suggested a role for a combined endoscopic and laparoscopic approach, using two or three intragastric trocars. This proved feasible for resection of GISTs of the oesophagogastric junction 42,43 . Still, it is a technically demanding procedure that requires advanced laparoscopic skills and instrumentation.…”
Section: Lesser Curvature and Gastro-oesophageal Junctionmentioning
confidence: 99%
“…El abordaje intrag谩strico encuentra su lugar en el caso de los GIST Tipo III, localizados en la curvatura menor o en la regi贸n de la uni贸n es贸fago-g谩strica (Tabla 1). Existen m煤lti-ples publicaciones constituidas por casos cl铆nicos o peque帽as series de casos que han demostrado la seguridad y validez de este abordaje o de sus variaciones [10][11][12][13][14][15][16][17][18][19][20] . Recientemente, este procedimiento tambi茅n se ha descrito mediante el uso de un solo puerto con la t茅cnica Single Incision Laparoscopic Surgery (SILS) con buenos resultados [21][22][23][24] .…”
Section: Discussionunclassified
“…Laparoscopic surgery for GIST is a controversial approach because injury of the pseudo-capsule during a laparoscopic procedure can result in tumor dissemination. However, several groups of investigators have reported that laparoscopic surgery for GIST \5 cm in size was safe and suitable [4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Various types of laparoscopic surgery for GIST have been described, including wedge resection of the stomach, intragastric tumor resection, and combined endoscopiclaparoscopic resection [4][5][6][7][8][9][10][11]. Wedge resection of the stomach is the ideal method for the GIST from the oncological aspect.…”
Section: Introductionmentioning
confidence: 99%